Molinosismo e desculpabilização - Tavares, Pedro Vilas Boas (1995)
The author proposes an historical reinterpretation of the Molinos phenomenon, based on a review of the literature on the subject since Massimo Petrocchi. Shifting from the Italian to the Portuguese context, it then goes on to characterize the kind of "quietism" persecuted by the Inquisition in this country, from the late 17th to the second decade of the 18th century.